SENAM VITALISASI OTAK UNTUK MENINGKATKAN FUNGSI KOGNITIF USIA DEWASA MUDA - Lisnaini, Lisnaini (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2021)
The purpose of the study. to know that exercise can enhance the function of the brain vitalization cogitif in young adulthood. Materials and methods. The sample selected from all the students of the Academy of Physiotherapy in accordance with the inclusion criteria, totaling 20 people. Given treatment vitalization brain gymnastics 16 times, 4 times a week for 4 weeks. Quasi-experimental research is a Group Designs with pre and post test design group designs. For the measurement of cognitive function that is used Digit Span subtest subtes Forward and Backward digit. Test statistical analysis used the Wilcoxon-test. Results. The function of cognition shows the mean pre-exercise 9.15 (± 1.7) and the mean value after gymnastics 15.85 (± 1.13). There is an increase in value of 6.7 Digit span after gymnastics vitalization brain (p <0.05). Conclusions. Gymnastics vitalization brain can improve cognitive function in young adults.